(untitled) (Research, Society and Development, 2022)
This paper aimed to evaluate the productivity of corn crop for silage, beans and straw production in different crop rotation systems with spring/summer and fall/winter green manures cultivated under agroecological production management. The experiment was implemented in a rural property managed in an agroecological system since 2009, in the 2017/18 and 2018 crops. The experimental design used was in randomized blocks, with five repetitions. The treatments consisted of four different crop rotation systems: monocrop corn/monocrop corn/fallow/beans; corn + cowpea/monocrop corn/oats/beans; corn + crotalaria/monocrop corn/forage radish/beans and corn + jack bean/monocrop corn/vetch/beans. After the 2018 second crop of corn was removed, the winter/spring green manures were sown: forage radish, vetch, and oats. This was followed in September by the bean crop. The dry matter yields of corn for silage in each growing season and of the bean were evaluated, as well as the total productivity of the systems. The straw yield was also evaluated. The crop rotation systems that included green manures presented the highest total productivity. The intercropping with pork bean favored the corn productivity in the harvest and the crotalaria stover favored the productivity in the off-season. The corn + cowpea/jack bean/beans monocrop and corn + crotalaria/jack bean/forage radish/beans systems favored the productivity of beans. The mode corn monocrop/corn monocrop/fallow did not prioritize the accumulation of straw on the soil.